XANTHINE OXIDASE INHIBITORY ACTIVITY OF RHUS MYSORENSIS LEAVES - K, Vivekanandan; E, Bhavya; C, Stalin (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The objective of this study was to assess the in vitro xanthine oxidase (XO) inhibiting activity of the methanolic leaf extract of the Rhusmysorensis. Methods: Uric acid is synthesized in the presence of XO which is an essential enzyme. Various concentrations of the leaf extract were taken. XO inhibiting activity was spectrophotometrically assayed. By increasing absorbance at 295 nm, the degree of enzyme spontaneity was determined. Results: Inhibition concentration 50 (IC50) of the methanolic extract of R. mysorensis leaves was 45.24Â±0.34 Î¼g/ml, compared with IC50 value of the standard allopurinol of 7.8Â±1.28 Î¼g/ml. Conclusion: Methanol extract of R. mysorensis can be used to treat hyperuricemia and gout after proper preclinical and clinical studies.